Endocannabinoid 2-Arachidonoylglycerol Synthesis and Metabolism at Neuronal Nuclear Matrix Fractions Derived from Adult Rat Brain Cortex - Aretxabala, Xabier; García del Caño, Gontzal; Barrondo, Sergio; López de Jesús, Maider; González-Burguera, Imanol; Saumell-Esnaola, Miquel; Goicolea, María Aranzazu; Sallés, Joan (International journal of molecular sciences, 2023)
In this report, we describe the kinetics characteristics of the diacylglycerol lipase-α (DGLα) located at the nuclear matrix of nuclei derived from adult cortical neurons. Thus, using high-resolution fluorescence microscopy, classical biochemical subcellular fractionation, and Western blot techniques, we demonstrate that the DGLα enzyme is located in the matrix of neuronal nuclei. Furthermore, by quantifying the 2-arachidonoylglycerol (2-AG) level by liquid chromatography and mass spectrometry when 1-stearoyl-2-arachidonoyl-sn-glycerol (SAG) was exogenously added as substrate, we describe the presence of a mechanism for 2-AG production through DGLα dependent biosynthesis with an apparent Km (Kmapp) of 180 µM and a Vmax of 1.3 pmol min−1 µg−1 protein. We also examined the presence of enzymes with hydrolytic and oxygenase activities that are able to use 2-AG as substrate, and described the localization and compartmentalization of the major 2-AG degradation enzymes, namely monoacylglycerol lipase (MGL), fatty acid amide hydrolase (FAAH), α/β-hydrolase domain 12 protein (ABHD12) and cyclooxygenase-2 (COX2). Of these, only ABHD12 exhibited the same distribution with respect to chromatin, lamin B1, SC-35 and NeuN as that described for DGLα. When 2-AG was exogenously added, we observed the production of arachidonic acid (AA), which was prevented by inhibitors (but not specific MGL or ABHD6 inhibitors) of the ABHD family. Overall, our results expand knowledge about the subcellular distribution of neuronal DGLα, and provide biochemical and morphological evidence to ensure that 2-AG is produced in the neuronal nuclear matrix. Thus, this work paves the way for proposing a working hypothesis about the role of 2-AG produced in neuronal nuclei.